A Comparison of Financial Performance and Islamicity Performance Index of Indonesian Syariah Commercial Banks Before and During the Covid-19 Pandemic - Istiqomah, Ayu; Khomsatun, Siti (Journal of Islamic Contemporary Accounting and Business, 2024)
This study aims to analyze the financial performance of Sharia commercial banks between before and during the covid-19 pandemic. This study uses an analysis of financial ratios and islamicity performance index to measure the financial performance. This study uses a quantitative method by using a comparative approach that compares the similarities or differences of three objects studied in a certain frame of mind. This study uses quarterly financial reports in 2018-2021. The population of this research is Islamic commercial banks that registered with OJK and issue quarterly financial reports. The statistical method used is the descriptive statistical test and Wilcoxon signed-rank test. The results show differences in the financial ratio (for KPMM, NPF, FDR, NI, and BOPO), islamicity performance index (for Profit Sharing Ratio and EDR_Qard & Donation) of Islamic commercial banks between before and during the pandemic